Improvement of Floc Quality and Tilapia (Oreochromis niloticus) Productivity in an Internet of Things (IoT)-Based Biofloc System - Cahyono, Indra; Mulyani, Sri; Rapi, Nuraini L.; S. Y., Hasyrif (Agrikan Jurnal Agribisnis Perikanan, 2024)
This study evaluates the impact of an IoT-based biofloc system on Nile tilapia aquaculture by comparing it to a conventional biofloc system. The experiment was conducted using two treatments: (1) biofloc with IoT-based monitoring for real-time dissolved oxygen (DO) and temperature control, and (2) conventional biofloc without IoT. Results showed that fish in the IoT system had higher growth (319.44 g, FCR 0.78) than those in the conventional system (236.67 g, FCR 1.19), due to more stable DO levels. Biofloc volume was also higher in the IoT system (34.14 ml/L vs. 22.73 ml/L), supporting microbial balance and natural feed availability. While temperature had no significant effect, IoT helped maintain environmental stability. These findings highlight IoT’s potential to enhance productivity, optimize feed conversion, and support aquaculture in the Industry 4.0 era.